A Case Of Miller-Fisher Syndrome Displaying A Fast Improvement Following Intravenous Immunglobuin Therapy - Yoldaş, Tahir; Yiğiter, Remzi; Bulut, Serpil; Ulvi, Hızır; Müngen, Bülent (Fırat University, 2002)
Miller-Fisher Syndrome is a rare and benign form of Guillain-Barre Syndrome and characterized by the acute onset of ophthalmoplegia, areflexia and ataxia. In our case, 28 year old male patient applied to our clinics with the complaints of double vision and gait imbalance. During the medical examination, bilateral total ophthalmoplegia, facial diplegia, truncal ataxia and areflexia were noticed. The results of the routine analyses of blood parameters, cranial computed tomography (CT) and magnetic resonance imaging (MRI) were normal. In the examination of cerebrospinal fluid, albuminocytologik dissociation was determined. Electromyography (EMG) results indicated the presence of sensorial neuropathy. The case was diagnosed as Miller-Fisher Syndrome and administered with intravenous immunglobuin (IVIG) at the dose of 400 mg/kg/day, for five days. On the third day of treatment, clinical symptoms stated to be ameliorated and on the 7 th day of the treatment, all the clinical symptom disappeared. EMG results obtained on 14 th day of treatment indicated a complete healing of the case.The results of this case indicate that IVIG treatment, compared to classical aproaches, seems a more effective and indespensable treatment option.

Akut başlayan oftalmopleji, arefleksi ve ataksi ile karakterize olan Miller-Fisher sendromu, Guillain-Barre sendromunun benign ve az görülen bir formdur. Çift görme ve dengesizlik şikayeti ile başvuran 28 yaşındaki erkek hastanın muayenesinde bilateral total oftalmopleji, fasial dipleji, gövde ataksisi ve arefleksi saptandı. Rutin kan tetikleri, kranial BT ve MRI normal olup, BOS muayenesinde albüminositolojik dissosiasyon, EMG de duysal nöropatiye uyan bulgular saptandı. Miller-Fisher sendromu tanısı alan hastaya 400 mg/kg/gün intravenöz immünglobulin (İVİG) 5 gün süreyle verildi. Tedavinin 3. günü klinik bulgularda düzelme başladı. 7. gün tüm klinik belirtiler kaybolmuştu. 14 gün sonraki EMG tetkiki tamamen normal bulundu. İVİG tedavisi bu tür olgularda klasik tedavi yöntemlerine göre çok daha etkili ve vazgeçilmez görünmektedir.
İNTRAVENÖZ İMMÜNGLOBULİN TEDAVİSİ İLE HIZLI İYİLEŞME GÖSTEREN BİR MİLLER FİSHER SENDROMU OLGUSU